Time-Related Grammatical Use by Children with SLI Across Languages: Beyond Tense - Leonard, Laurence B. (Int J Speech Lang Pathol, 2015)
PURPOSE: For years, investigators have studied the use of tense by children with specific language impairment (SLI). This review article provides a summary of research on the use of other time-related grammatical forms by these children. METHODS: The literature on children’s use of grammatical and lexical aspect, modal verbs, and temporal adverbs is reviewed. Findings from children with SLI acquiring a range of different languages are considered. RESULTS: Grammatical aspect and lexical aspect appear to be special weaknesses in children with SLI, and problems with lexical aspect may also have an adverse effect on these children’s ability to use past tense morphology. Although children with SLI are below age level in their use of modal verbs and temporal adverbs, the available evidence suggests that these weaknesses are no greater than these children’s more general limitations with language. CONCLUSIONS: The evidence thus far indicates that time-related notions farther on the morphosyntactic end of the language continuum (aspect) are more problematic for these children than those time-related notions (modals, temporal adverbs) that include a pragmatic and/or semantic component. In some languages, aspect may prove to be a useful clinical marker of this disorder.